Dermatofibrosarcoma Protuberans - Acosta, Alvaro E.; Vélez, Catalina Santa (Current treatment options in oncology, 2017)
Opinion statement Dermatofibrosarcoma protuberans (DFSP) is a slow growing tumor with a very low metastatic potential but with significant subclinical extension and great capacity for local destruction. Thus, the first surgeon approached with such challenging tumor must attempt to cure the patient with a method that spares healthy tissue and ensures an optimal oncological, functional, and esthetic result. The treatment of DFSP often requires a multidisciplinary approach. Depending on location, dermatologic surgeons, surgical oncologists, head and neck surgeons, neurosurgeons, plastic surgeons, and occasionally medical oncologists may be involved with the management. Mohs micrographic surgery (MMS) is the preferred method when available. In our institution, most of the DFSP cases are often advanced cases; thus, dermatologic surgeons obtain clear margins peripherally and other surgical specialties assist with resection of the fascia and any critical deeper structures. When MMS is not available, wide local excision (at least 2- to 3-cm margins of resection) with exhaustive pathologic assessment of margin status is recommended, and it is best to confirm tumor extirpation prior to any reconstruction. Subclinical extension of the tumor could be related to the size; how long it has been growing or histological markers that are unknown right now. No clinical trials comparing MMS vs WLE are available, and further research should be focused on these subjects as well as the use of imatinib and other targeted therapies for recurrent and metastatic tumors and for neoadjuvant treatment.